Progress in preclinical studies of macrophage autophagy in the regulation of ALI/ARDS - Liu, Chang; Xiao, Kun; Xie, Lixin (Frontiers in Immunology, 2022)
Acute lung injury (ALI)/acute respiratory distress syndrome (ARDS) is a critical clinical syndrome with high morbidity and mortality that poses a major challenge in critical care medicine. The development of ALI/ARDS involves excessive inflammatory response, and macrophage autophagy plays an important role in regulating the inflammatory response in ALI/ARDS. In this paper, we review the effects of autophagy in regulating macrophage function, discuss the roles of macrophage autophagy in ALI/ARDS, and highlight drugs and other interventions that can modulate macrophage autophagy in ALI/ARDS to improve the understanding of the mechanism of macrophage autophagy in ALI/ARDS and provide new ideas and further research directions for the treatment of ALI/ARDS.